Should academia care about online reputation management and monitoring? - Matešić, Marija (Array, 2010)
Reputation management has always been important for individuals, companies and organizations. Emergence of new types of media, as is the social media, brought radical changes in the ways we manage and monitor personal, corporate and organizational reputation. The fundamental purpose of this study is to describe how social media influences corporate and organizational culture in respect of reputation management and monitoring. It is also discussed how Academia and their stakeholders should be part of these changes.